Improving the Performance of User Search Goals Using Noval Approach - Harilakshmanraj, J. S. (Asian Journal of Engineering and Applied Technology, 2014)
World Wide Web acts as storage repository and it used for an information retrieval. while, fetching information through user queries, a search engine in a large and un-effective collection of document. To avoid these conflict and to improve the search engine, I propose Novel based approach. This approach states two strategies: clustering and prioritation. Based on the user search goals the information is been restructured dynamically and it is been clustered and based on ranking algorithm, it has been prioritized.